Fentanyl-induced reward seeking is sex and dose dependent and is prevented by D-cysteine ethylester - Knauss, Zackery T.; Hearn, Caden J.; Hendryx, Nathan C.; Aboalrob, Fanan S.; Mueller-Figueroa, Yazmin; Damron, Derek S.; Lewis, Stephen J.; Mueller, Devin (Frontiers in Pharmacology, 2023)
Despite their inclination to induce tolerance, addictive states, and respiratory depression, synthetic opioids are among the most effective clinically administered drugs to treat severe acute/chronic pain and induce surgical anesthesia. Current medical interventions for opioidinduced respiratory depression (OIRD), wooden chest syndrome, and opioid use disorder (OUD) show limited efficacy and are marked by low success in the face of highly potent synthetic opioids such as fentanyl. D-Cysteine ethylester (D-CYSee) prevents OIRD and post-treatment withdrawal in male/female rats and mice with minimal effect on analgesic status. However, the potential aversive or rewarding effects of D-CYSee have yet to be fully characterized and its efficacy could be compromised by interactions with opioid-reward pathology. Using a model of fentanyl-induced conditioned place preference (CPP), this study evaluated 1) the dose and sex dependent effects of fentanyl to induce rewarding states, and 2) the extent to which D-CYSee alters affective state and the acquisition of fentanyl-induced seeking behaviors. Fentanyl reward-related effects were found to be dose and sex dependent. Male rats exhibited a range-bound dose response centered at 5 µg/kg. Female rats exhibited a CPP only at 50 µg/kg. This dose was effective in 25% of females with the remaining 75% showing no significant CPP at any dose. Pretreatment with 100 mg/kg, but not 10 mg/kg, D-CYSee prevented acquisition of fentanyl seeking in males while both doses were effective at preventing acquisition in females. These findings suggest that D-CYSee is an effective co-treatment with prescribed opioids to reduce the development of OUD.